2010
DOI: 10.1243/09544097jrrt367
|View full text |Cite
|
Sign up to set email alerts
|

An Inspection of Railway Ballast Quality Using Ground Penetrating Radar in Finland

Abstract: The maintenance of heavy haul railway lines causes considerable cost and in many cases difficulties to rail traffic. Railway infrastructure management in Finland is important because in many locations the same railway lines are used by both freight and passenger trains. Along with the mixed traffic, the cold climate presents challenges in keeping the track in good condition. There is a great demand for economical and non-destructive methods that provide continuous condition information of track structure. In r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 2 publications
2
38
0
4
Order By: Relevance
“…The reflected energy, originating from the interfaces between materials of different dielectric properties, is received and recorded for analysis. GPR data consists of changes in reflection amplitude, changes in the arrival time of specific reflections, and signal attenuation [32,38]. The method provides a continuous profile of the thickness and properties of railway structures, which can be used to analyse the quality of track substructures, such as the moisture susceptibility of ballast and subballast, fouling of ballast, layer deformation, and mud pumping [39][40][41].…”
Section: Introduction Of Gprmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflected energy, originating from the interfaces between materials of different dielectric properties, is received and recorded for analysis. GPR data consists of changes in reflection amplitude, changes in the arrival time of specific reflections, and signal attenuation [32,38]. The method provides a continuous profile of the thickness and properties of railway structures, which can be used to analyse the quality of track substructures, such as the moisture susceptibility of ballast and subballast, fouling of ballast, layer deformation, and mud pumping [39][40][41].…”
Section: Introduction Of Gprmentioning
confidence: 99%
“…The processing, visualization, interpretation, and analysis of the GPR data are performed using the Rail Doctor software (version 3.2), developed by Roadscanners Oy, Rovaniemi, Finland, 2017. The measurement system has been calibrated against sample analysis [38] and pit tests [39]. A screenshot from the recorded video is shown in Figure 4a, wherein a transition zone consisting of embankment and a bridge can be found.…”
Section: Introduction Of Gprmentioning
confidence: 99%
“…In some countries, GPR tests have been performed along tracks with the aim of detecting zones with problems in both ballast and subsoil layers. First results have shown that GPR is a reliable technique to assess track geometry problems and consequently to improve maintenance planning [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, GPR data provide further information that could be used in order to deter- 34 mine the inner conditions and characteristics about materials. In this paper, the possible analysis of the 35 frequency spectrum of GPR signals is analysed and discussed. Several tests were carried out in a portion 36 of a highway in two different stages of its service life.…”
mentioning
confidence: 99%
“…The method is based on determining the stiffness modulus of 49 each layer that makes up the pavement using back-calculation in 50 order to obtain the state of stress and strain in significant points [3]. and locating cavities beneath the structure of a road (e.g., [5][6][7][8] to concrete [32,33], to ballast for railway infrastructure [34,35] 168 and to other media [36]. 169 Other studies have analysed the alterations in the frequency 170 spectra as the ratio of two materials changes.…”
mentioning
confidence: 99%